Exploring the sources of loan default clustering using survival analysis with frailty - Enrique Bátiz-Zuk; Abdulkadir Mohamed; Fátima Sánchez-Cajal (Banco de México, 2021)
This paper investigates whether three microeconomic loan characteristics are sources of loan default clustering in the Mexican banking sector by employing survival analysis with frailty. Using a large sample of bank loan level data granted to micro, small and medium sized firms from January 2010 to 2018, we test whether classifying loans by the bank's systemic importance, industry or at individual firm level enhances the predictions of loans defaults. Our results show that loans granted by Domestic Systemically Important Banks contribute to the default clustering in micro and small firm loans. This is due to aggregate default rate levels and clusters that are large for these firms loans compared with loans provided to medium-sized firms. These findings have important implications for bank's expected loss management related to the correlated loan default risk.
Keywords: C53; C41; C25; G38; 330; Credit risk; Parametric survival analysis; Accelerated Failure Time (AFT) models; Shared frailty models; IFRS 9